First demonstration of photoelectrochemical water splitting by commercial W–Cu powder metallurgy parts converted to highly porous 3D WO3/W skeletons. (28th February 2020) - Mojaddami, Majdoddin; Simchi, Abdolreza
Abstract: Hydrogen evolution through photoelectrochemical (PEC) water splitting by tungsten oxide-based photoanodes, as a stable and environmental-friendly material with moderate band gap, has attracted significant interest in recent years. The performance of WO3 photoanode could be hindered by its poor oxygen evolution reaction kinetics and high charge carrier recombination rate. Additionally, scalable and cost-effective commercial procedure to prepare nanostructured electrodes is still challenging. We present, for the first time, a novel and scalable method to fabricate highly efficient self-supported WO3 /W nanostructured photoanodes from commercial W–Cu powder metallurgy (P/M) parts for water splitting. The electrodes were prepared by electrochemical etching of Cu networks followed by hydrothermal growth of WO3 nanoflakes. Interconnected channels of W skeleton provided high active surface area for the growth of WO3 nanoflakes with a thickness of ~40 nm and lateral dimension of ~250 nm. The optimized photoelectrode having 35% interconnected porosity exhibited an impressive current density of 4.36 mA cm −2 comprising a remarkable photocurrent of 1.71 mA cm −2 at 1.23 V vs. RHE under 100 mW cm −2 simulated sunlight. This achievement is amongst the highest reported photocurrents for WO3 photoelectrodes with tungsten substrate reported so far. Impedance and Mott-Schottky analyses evidenced fast charge transfer, low recombination rate, and accelerated O2 detachment provided by optimum 3D porous WO3 /W electrode. Due to the nature of the commercial P/M parts and low-temperature hydrothermal processing, the procedure is cost-effective and scalable which can pave a new route for the fabrication of highly porous and efficient water splitting electrodes. Graphical abstract: Image 1 Highlights: Highly porous 3D WO3 /W was prepared from commercial P/M W-Cu parts. A remarkable photocurrent of 1.71 mA cm -2 at 1.23 VRHE was achieved. Effects of interconnected pores on electrochemical activity of nanoflakes were shown. EIS determined excellent charge transfer and transport properties within 3D skeletons.